Cholesterol biosynthesis supports the growth of hepatocarcinoma lesions depleted of fatty acid synthase in mice and humans. Issue 1 (6th April 2019) - Che, Li; Chi, Wenna; Qiao, Yu; Zhang, Jie; Song, Xinhua; Liu, Ye; Li, Lei; Jia, Jiaoyuan; Pilo, Maria G; Wang, Jingxiao; Cigliano, Antonio; Ma, Zhilong; et al.
Abstract : Objective: Increased de novo fatty acid (FA) synthesis and cholesterol biosynthesis have been independently described in many tumour types, including hepatocellular carcinoma (HCC). Design: We investigated the functional contribution of fatty acid synthase (Fasn)-mediated de novo FA synthesis in a murine HCC model induced by loss of Pten and overexpression of c-Met (sgPten/c-Met) using liver-specific Fasn knockout mice. Expression arrays and lipidomic analysis were performed to characterise the global gene expression and lipid profiles, respectively, of sgPten/c-Met HCC from wild-type and Fasn knockout mice. Human HCC cell lines were used for in vitro studies. Results: Ablation of Fasn significantly delayed sgPten/c-Met-driven hepatocarcinogenesis in mice. However, eventually, HCC emerged in Fasn knockout mice. Comparative genomic and lipidomic analyses revealed the upregulation of genes involved in cholesterol biosynthesis, as well as decreased triglyceride levels and increased cholesterol esters, in HCC from these mice. Mechanistically, loss of Fasn promoted nuclear localisation and activation of sterol regulatory element binding protein 2 (Srebp2), which triggered cholesterogenesis. Blocking cholesterol synthesis via the dominant negative form of Srebp2 ( dnSrebp2 ) completely prevented sgPten/c-Met-driven hepatocarcinogenesis in Fasn knockout mice. Similarly, silencing of FASN resulted in increased SREBP2 activation and hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase ( HMGCR) expression in human HCC cell lines. Concomitant inhibition of FASN-mediated FA synthesis and HMGCR-driven cholesterol production was highly detrimental for HCC cell growth in culture. Conclusion: Our study uncovers a novel functional crosstalk between aberrant lipogenesis and cholesterol biosynthesis pathways in hepatocarcinogenesis, whose concomitant inhibition might represent a therapeutic option for HCC.